The Wisconsin frontier - Wyman, Mark (History of the trans-Appalachian frontier., 1998)
From French coureurs de bois coursing through its waterways in the seventeenth century to the lumberjacks who rode logs down those same rivers in the late nineteenth century, settlers came to Wisconsin's frontier seeking wealth and opportunity. Indians mixed with these newcomers, sometimes helping and sometimes challenging them, often benefiting from their guns, pots, blankets, and other trade items. The settlers' frontier produced a state with enormous ethnic variety, but its unruliness worried distant governmental and religious authorities, who soon dispatched officials and missionaries to help guide the new settlements.